1999
DOI: 10.1097/00007632-199908010-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Somatosensory- and Motor-Evoked Potentials in Predicting and Monitoring the Effect of Therapy in Spondylotic Cervical Myelopathy

Abstract: Longitudinal evoked potentials showed limited use for evaluating the results of therapy in an individual patient. They could be useful in the group assessment of therapy results and in labeling a subgroup of patients with potentially favorable postsurgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 26 publications
0
31
0
1
Order By: Relevance
“…The studies described by Bednarik et al 1 and Kadanka and colleagues 3 appear to concern the same group of patients. However, the Bednarik et al study included electrophysiological data in addition to clinical outcome data.…”
Section: Mild Cervical Myelopathymentioning
confidence: 80%
See 1 more Smart Citation
“…The studies described by Bednarik et al 1 and Kadanka and colleagues 3 appear to concern the same group of patients. However, the Bednarik et al study included electrophysiological data in addition to clinical outcome data.…”
Section: Mild Cervical Myelopathymentioning
confidence: 80%
“…The subgroup of 12 patients with severe disability (mean mJOA scale score of 9.5) showed significant improvement after surgical intervention (mean mJOA scale score 10.9 at 2 years postoperatively). 1,3 Because of its small size, this study was powered to have a minimal detectable difference in mJOA scale score of 1.7. With pretreatment mJOA scores starting at ~ 14 out of a possible 18, the level of improvement would have to be 42% (1.7/4.0) for the study to have a detectable a difference; this raises the likelihood of a Type II error.…”
Section: Mild Cervical Myelopathymentioning
confidence: 99%
“…Authors of various studies have suggested that MEPs, SEPs, and other forms of neurophysiological monitoring may potentially provide prognostic information regarding the clinical outcome of decompression surgery in patients with CSM. 1,4,9,10,12,13 Lyu and colleagues 12 performed preoperative MEPs and SEPs in 39 patients with CSM who had hyperintensity on T2-weighted MR images of the cervical cord and who were to undergo surgical decompression. The authors used pre-and postoperative JOA scale scores 19 and 6-month neurological recovery rates as described by Hirabayashi et al 8 as functional outcome measures.…”
Section: Neurophysiological Functionmentioning
confidence: 99%
“…Bednarik et al 1 divided a group of 61 patients with CSM into 2 groups according to myelopathy severity. Forty-nine patients had mild or moderate myelopathy (mJOA scale score ≥ 12), and 12 had severe myelopathy (mJOA scale score < 12).…”
Section: Neurophysiological Functionmentioning
confidence: 99%
“…In smaller studies, adults with cervical myelopathy had about a 12% incidence of MEP only alerts (no EMG or SEP changes); these alerts were usually followed by resolution after alterations in anesthetic and surgical management occurred. Nonetheless, the authors believed that the MEP monitoring provided 100% sensitivity and 90% specificity [ 46,47 ] .…”
Section: Application Of Mep Monitoringmentioning
confidence: 99%